2011
DOI: 10.1603/me10057
|View full text |Cite
|
Sign up to set email alerts
|

Bovicola tibialis(Phthiraptera: Trichodectidae): Occurrence of an Exotic Chewing Louse on Cervids in North America: Table 1.

Abstract: Through a recent (2003-2007) survey of ectoparasites on hoofed mammals in western North America, a literature review, and examination of archived museum specimens, we found that the exotic deer-chewing louse, Bovicola tibialis (Piaget), is a long-term, widespread resident in the region. The earliest known collection was from Salt Spring Island, Canada, in 1941. We found these lice on the typical host, that is, introduced European fallow deer (Dama dama L.), and on Asian chital (Axis axis [Erxleben] ), native C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…14 Over the past 2 decades, EPOD in deer has spread from Washington to California, and the range of the lice continues to expand. In 2009 and 2011, respectively, B. tibialis was detected in Riggins in western Idaho, Box Butte County in Nebraska, Carbon County in Wyoming, 18 Fallon in western Nevada, Tonopah in central Nevada, and Baker in eastern Nevada (P Wolff, Nevada Department of Wildlife, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Over the past 2 decades, EPOD in deer has spread from Washington to California, and the range of the lice continues to expand. In 2009 and 2011, respectively, B. tibialis was detected in Riggins in western Idaho, Box Butte County in Nebraska, Carbon County in Wyoming, 18 Fallon in western Nevada, Tonopah in central Nevada, and Baker in eastern Nevada (P Wolff, Nevada Department of Wildlife, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…Examined deer from the herd were infested with B. tibialis and L. africanus lice, 18 and had mild to severe hair loss, verminous pneumonia, and copper and selenium deficiencies (CDFW, unpublished observations).…”
Section: Department Of Fish and Wildlife [Cdfw] Pers Comm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower survival of HLS fawns may be because of poor body condition, as they were found to have lower body condition scores (Murphie ) similar to observations from other studies (Bildfell et al , Foreyt et al ). Fawns with HLS were likely compromised by the loss of hair, which increased their thermoregulatory costs, reduced fat stores, weakened their immune responsiveness (Bildfell et al , Mertins et al ), and increased their risk of predation and other natural mortality factors.…”
Section: Discussionmentioning
confidence: 99%
“…to mule deer and the subsequent development of HLS. Mertins et al () reported extensive hair loss in tule elk ( C. canadensis nannodes ) in California and a necropsy found Damalania ( Cervicola ) sp. We documented heavy infestations of Damalania ( Cervicola ) sp.…”
Section: Discussionmentioning
confidence: 99%